Auditoría modalidad regular vigencia 2014 a la ESE Hospital Departamental San Juan de Dios, en desarrollo del plan general de auditoría de la vigencia fiscal 2015 (2015)
The regular review auditing is the examination conducted by audit institutions to operations of different nature, made by control subjects in order to give a comprehensive opinion formed by the opinion of financial and management statements concepts, also by the results. So we can give an opinion about the management conclusions of the account. For the particular case of this internship regular auditing was conducted at the ESE Hospital Departamental Universitario San Juan de Dios, 2.014 period, based on the territorial auditing guide (GAT) adopted by Resolution No. 207 of December 20, 2012, in the auditing was taken each of the stages, starting from the planning stage where it is verified all the information rendered in physical and magnetic media through the SIA application to verify the quality of the information, where it was noted that some of the formats did not have the requested information, therefore it was required by the control authority.